The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5935/medicalexpress.2016.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Social networking, a new online addiction: a review of Facebook and other addiction disorders

Abstract: INTRODUCTION: Facebook is the world's most widely accessed social network, where millions of people intercommunicate. Behavioral and psychological changes relate to abusive and uncontrolled use creating severe impacts on users' life. METHOD: A critical revision was performed through MedLine, Lilacs, SciELO and Cochrane databases using the terms: "Facebook Addiction, " "Social Network Sites, " "Facebook Abuse. " The search covered the past 5 years up to January 2015. Articles that examine dependence on Facebook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 31 publications
1
26
0
2
Order By: Relevance
“…A internet favorece a comunicação e a busca de informações e além disso é uma importante ferramenta de contato social 12,13 . Desde a década de 1990, a internet tornou-se parte essencial do cotidiano 15 .…”
Section: Discussionunclassified
“…A internet favorece a comunicação e a busca de informações e além disso é uma importante ferramenta de contato social 12,13 . Desde a década de 1990, a internet tornou-se parte essencial do cotidiano 15 .…”
Section: Discussionunclassified
“…Previous studies for example demonstrated the relationship between ICD symptoms and depression as well as social anxiety (De Cock et al, 2013; Panek et al, 2013; Hong et al, 2014; Bodroza and Jovanovic, 2015; Laconi et al, 2015; Moreau et al, 2015; Guedes et al, 2016). Shyness and low self-esteem have also been linked to ICD symptoms in general or Facebook addiction in particular (Chak and Leung, 2004; Steinfield et al, 2008; Omar and Subramanian, 2013; Panek et al, 2013; Bhagat, 2015; Laconi et al, 2015; Guedes et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…In contrast to SNS, social games and information search are not main features of communication applications. (Amichai-Hamburger and Vinitzky, 2010; Kuss and Griffiths, 2011b; Floros and Siomos, 2013; Guedes et al, 2016). However, there is a growing amount of individuals experiencing negative consequences due to excessive use of the Internet or various online applications, such as online communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aggravated internet use and anxiety in these patients, a fact that had also been observed in other studies. 48,49 Our study found a higher prevalence rate of women in the treatment group (29 women, 13 men); the control group presented a 50-50 score of 21 men and 21 women. Only two studies showed this difference in prevalence rate among males and females, presenting higher rates in females 48,50 while most studies found either a higher prevalence among males 51,52 or equal prevalence.…”
Section: ■ Resultsmentioning
confidence: 49%